Tobacco consumption, environmental tobacco smoke exposure and illicit drug use: A study on selected south Asian countries / Mohammad Alamgir Kabir - Kabir, Mohammad Alamgir (2014)

(untitled)
The trend of tobacco consumption (TC) is on the increase in the developing and under-developed countries including South Asian region. TC and the closely related problems of environmental tobacco smoke (ETS) exposure and illicit drug use (IDU) are increasingly alarming in South Asian countries. This study aims to explore the prevalence, patterns and determinants of (i) TC among youths and adults, (ii) ETS exposure among adults at home, workplace and public places, and (iii) IDU among males in selected South Asian countries. The associations between TC and ETS, and TC and IDU were also examined. This study utilized data from (i) Global Youth Tobacco Survey-2007 that covered 2,242 Bangladeshi, 1,444 Nepalese and 1,377 Sri Lankan youths aged 13–15 years, (ii) Global Adult Tobacco Survey-2010 that covered 9,629 Bangladeshi and 69,296 Indian adults aged 15 years or more, (iii) Bangladesh Demographic and Health Survey-2007 that covered 3,771 males aged 15-54 years, and (iv) Bangladesh Urban Health Survey-2007 that covered 1,576 males aged 15-24 years that lived in urban slums. Univariate, bivariate, and multivariate (binary, ordinal, and multinomial logistic regressions) and classification and regression tree (CART) analyses and diamond-shaped equiponderant graphs were used for analysis. Prevalence of youth TC was 6.9% in Bangladesh, 9.4% in Nepal and 9.1% in Sri Lanka with higher rates among males. Common significant predictors include TC among friends, exposure to smoking at home and other places, and teaching of smoking hazards in schools. Availability of free tobacco products from vendors significantly influenced Bangladeshi and Sri Lankan youths. Prevalence of adult TC was 43.3% in Bangladesh and 34.6% in India. Males and those older had a higher tendency to use tobacco products. Adults with no education were more likely to use tobacco products in Bangladesh (odds ratio, OR=4.9) and India (OR=3.0) compared to others with tertiary iv education. Adults with the poorest wealth status were more likely to consume tobacco products in Bangladesh (OR=2.3) and India (OR=3.0) compared to those from the richest wealth status. Better knowledge, attitude and perception towards TC significantly reduced the TC rates in both countries. CART analysis had the highest classification accuracy for characterizing smoking patterns. Age of TC initiation, wealth status and gender were important variables for classifying smoking behavior. Other classifying variables include place of residence, educational attainment, and warnings printed on packaging of tobacco products. Older adults and females had significantly less exposure to ETS in Bangladesh and India. Larger family size increased the chance of exposure at home. Those with higher education and knowledge on ETS had lower chance of exposure at home and workplaces, but they had higher exposure at public places. Smoking ban at home and workplaces significantly reduced the chances of being exposed to ETS. The results also suggested that TC increased the likelihood of exposure to ETS, and a higher frequency of TC tend to worsen the problem. Prevalence of IDU among young males in urban slums and the general male population in Bangladesh were 9.1% and 3.4%, respectively. Significant predictors of IDU include education, duration of living in slums, and sexually transmitted infections. The logistic regression analysis revealed that those who used tobacco products daily had significantly higher likelihood of IDU. This likelihood also increased significantly with frequency of tobacco use. The impact of TC on IDU was remarkably higher among males in slums compared to the general male population. Understanding of the influencing factors of TC, ETS and IDU provides helpful insights for tobacco control policy formulation in South Asian region, as well as policy lessons for other low and low-middle income countries.